Frequency of driver oncogenic alterations in NSCLC and estimated indoor radon exposure in Europe (RADON EUROPE study) - Miguel García-Pardo; Marta García de Herreros; Edouard Auclin; Miquel Ferriol-Galmes; Juan Carlos Laguna; Teresa Gorría; Gerard Caravaca; Joan Sart; Víctor Albarrán-Artahona; Rafael López-Castro; Cristina Teixidó; Giancarlo Castellano; et al. (Therapeutic Advances in Medical Oncology, 2025)
Background: Geographical variations in the frequency of oncogenic driver alterations in non-small cell lung cancer (NSCLC) are observed worldwide, likely influenced by genetic and environmental factors. Radon, a leading cause of lung cancer in nonsmokers, may influence NSCLC’s molecular profile. Objectives: This study aims to explore the potential correlation between estimated indoor radon concentrations and the frequency of driver alterations in NSCLC across Europe. Design: Ecological study of European countries with available data on indoor radon exposure (estimated mean levels and the proportion (%) of dwellings with concentrations >200 and >400 Bq/m 3 ), and frequency of NSCLC actionable genomic alterations ( EGFR , ALK ) from PubMed articles and meeting abstracts with sample size >100 patients. Methods: We retrospectively analyzed NSCLC molecular data and radon exposure levels from European countries. Radon data, including the mean and proportion (%) of dwellings with concentrations >200 and >400 Bq/m 3 , were sourced from the European Commission Report 2005. NSCLC molecular alteration frequency ( EGFR , ALK ) was extracted from PubMed articles with sample sizes >100 patients. The correlation between molecular alteration frequencies and country-specific radon data were assessed. Results: Data on radon exposure and EGFR / ALK frequency were available for 21 European countries. Five countries had mean radon levels >100 Bq/m 3 , and eight countries had ⩾3% of dwellings with concentrations >400 Bq/m 3 . The median frequency of EGFR mutations and ALK fusions was 11.3% (range 7%–18.1%) and 4.1% (range 3.4%–12%), respectively. A positive correlation was found between estimated ALK -fusion frequency and the percentage of dwellings with >400 Bq/m 3 ( r  = 0.72, p  = 0.001). No correlation was found between EGFR mutation frequency and radon exposure. Conclusion: We found a positive correlation between estimated ALK fusion frequency in NSCLC and the proportion of dwellings exceeding 400 Bq/m 3 radon exposure in 21 European countries. Further research is needed to explore the potential influence of radon and other environmental factors on NSCLC with driver alterations.